Different is better: how unique initial coin offering language in white papers enhances success. (22nd February 2021) - Yen, Ju‐Chun; Wang, Tawei; Chen, Yu‐Hung
Abstract: This study examines whether the unique and common content of initial coin offering (ICO) white papers is related to ICO fund raising and post‐ICO trading activities. Based on the signalling theory, we expect that high‐quality ICOs can provide more unique content in their white papers to distinguish themselves from low‐quality ICOs because it may be costly for low‐quality ICOs to provide unique and specific information. Our results show that ICOs that have more unique or less common content in their white papers raise more funds or are subject to more active trading and higher market values in the post‐ICO period.